The Result of Covid-19 Spreads in Education World - Molla , Nur Laila (South Asian Journal of Social Sciences and Humanities, 2021)
COVID-19 is the most devastating pandemic in human history. Every aspect of human life on earth is disrupted, with little or no education. Many countries have decided to close schools, colleges, and universities, including Indonesia. The crisis came as a shock to governments in every part of the world, including Indonesia, which had to make drastic decisions to close their schools and save lives or to reopen schools in order to save workers’ livelihoods. The purpose of this study was to analyze the impact of the spread of covid-19 in the world of education. 75 respondents used for sample. The sample selection method used was the target sample. An analytical tool used to assess product duration and determination. Test results show that the spread of Covid-19 has a positive impact on the education world. The study found that the spread of covid-19 affects the world of education.